2018
DOI: 10.1523/jneurosci.3261-17.2018
|View full text |Cite
|
Sign up to set email alerts
|

The Neuroregenerative Capacity of Olfactory Stem Cells Is Not Limitless: Implications for Aging

Abstract: The olfactory epithelium (OE) of vertebrates is a highly regenerative neuroepithelium, maintained under normal condition by a population of stem and progenitor cells - globose basal cells (GBCs) that also contribute to epithelial reconstitution after injury. However, aging of the OE often leads to neurogenic exhaustion - the disappearance of both GBCs and olfactory sensory neurons (OSNs). Aneuronal tissue may remain as olfactory, with an uninterrupted sheet of apically arrayed microvillar-capped sustentacular … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
63
0
2

Year Published

2019
2019
2023
2023

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 58 publications
(68 citation statements)
references
References 57 publications
3
63
0
2
Order By: Relevance
“…This study is the only reported exploitation of OE stem cells in AD research. Note that in both mice and humans the OE tends to lose its neuroregenerative ability with age (Child et al, 2018): GBCs somehow run out, HBCs alone are no longer sufficient, and the OE becomes nonneurogenic (Schwob et al, 2017).…”
Section: Olfactory System Neuroregeneration In Alzheimer's Diseasementioning
confidence: 99%
“…This study is the only reported exploitation of OE stem cells in AD research. Note that in both mice and humans the OE tends to lose its neuroregenerative ability with age (Child et al, 2018): GBCs somehow run out, HBCs alone are no longer sufficient, and the OE becomes nonneurogenic (Schwob et al, 2017).…”
Section: Olfactory System Neuroregeneration In Alzheimer's Diseasementioning
confidence: 99%
“…Interestingly, the inflammatory reaction to xenobiotics contributes to the neurogenesis of basal progenitors stem cells through the macrophages-mediated release of TNF-Îą and nuclear factor kappa-light-chain-enhancer of activated B cells (NFk-B) (Borders et al, 2007;Chen et al, 2017). As for other organs the regenerative capacity of the olfactory neuroepithelium decays with aging both in humans and rodents (Child et al, 2018;Holbrook et al, 2011;Kondo et al, 2010), limiting the neurogenesis-promoting action of the innate immunity, while maintaining the inflammatory effect. This scenario is common in patients with chronic rhinosinusitis with hyposmia or transient anosmia, showing structurally and functionally altered neuroepithelium (Doty and Mishra, 2001).…”
Section: Olfactory Gateway Of Peripheral To Central Inflammatory Respmentioning
confidence: 99%
“…The depletion of neural stem cells attributed to accelerated proliferation has been reported in an induced neural degeneration mouse model, suggesting that the neuroregenerative capacity of neural stem cells is limited. 45 Our results indicating long-term effects of TBI on hippocampal neurogenesis and ability of generating immature neurons at the chronic stage after TBI are demonstrated by the significant reduction in the DCX-positive immature neurons in the DG 28 days post-injury.…”
Section: Discussionmentioning
confidence: 52%